THE EFFECT OF VOCABULARY NOTEBOOK IN ENRICHING STUDENTS’ VOCABULARY AT THE 3RD SEMESTER STUDENTS OF PSDKU ARU - Salmon J Hukom (PEDAGOGIKA: Jurnal Pedagogik dan Dinamika Pendidikan, 2023)
The aim of conducting this research is to see the effect of using the Vocabulary Notebook strategy in enriching students’ vocabulary. The research was done for three months with 12 students as samples. The research method was experimental research with pre-test and post-test that were used to take the data. The description of statistics and inferential statistics were used to analyze the data, and the SPSS program also was used in the process of analyzing data. The results show that the mean value in the pre-test was 15.42 with a deviation standard was 2.64, while the mean value in the post-test was 41.92 with a standard error of 0.85. Thus, it can be said that the results of the post-test were higher than the pre-test. Moreover, the significant value (2 tailed) of the research was 0.000(p 0.05), so the results of the pre-test and post-test have a significant change. All in all, there is a significant difference between pre-test and post-test after getting treatment using the Vocabulary Notebook strategy in enriching students' vocabulary. Thus, the hypothesis of this study is accepted.